COVID-19 Genetic and Environmental Risk Factors: A Look at the Evidence - Abdelzaher, Hana; Saleh, Basma M.; Ismail, Hebatalla A.; Hafiz, Marwa; Gabal, Macy Abou; Mahmoud, Miranda; Hashish, Sarah; Gawad, Rana M. Abdel; Gharieb, Rami Y.; Abdelnaser, Anwar (Frontiers in Pharmacology, 2020)
The Covid-19 pandemic is with no doubt the biggest health crisis of the 21st century. The disease is caused by a virus of the Coronaviridae family and is closely related to the virus responsible for the severe acute respiratory Syndrome (SARS). Since December 2019, the virus has continued to spread way beyond the location of the first recorded cases (Wuhan, China). As of now, over 5 million cases have been diagnosed with the disease worldwide and over 300 thousand have died. COVID-19 patients suffer from respiratory symptoms that can rapidly turn into potentially fatal acute respiratory distress syndrome (ARDS) in a portion of patients. Although many drugs and vaccines are currently under clinical trials, there is no currently approved treatment or vaccine. It is therefore critical to correctly identify risk factors that lead to the exacerbation of symptoms in highly susceptible groups. Groups that are at high risk include those aged 55 or older especially those with underlying conditions such as cardiovascular diseases. Certain ethnicities such as African-Americans have been found to be at a higher risk and males seem to be higher both in numbers as well as severity of cases. It is hypothesized that these groups are at risk as their molecular landscape is more permissive of viral infection and growth. Different occupations, especially those related to health-care as well as populations that do not cultivate a mask-wearing culture are at higher risk due to environmental exposure. In this article, we examine the evidence regarding different groups that are more sensitive to the disease and review hypotheses pertaining to COVID-19 infection and prognosis. Risk factors that can be related to the molecular landscape of COVID-19 infection as well as those related to environmental and occupational conditions are discussed.